2020
DOI: 10.1017/s1460396920000825
|View full text |Cite
|
Sign up to set email alerts
|

Bullous pemphigoid development during the course of breast cancer: a radiation induced or a radiation recall dermatitis?

Abstract: Background: Bullous pemphigoid (BP) is the most common autoimmune bullous disease, which is usually seen in older ages. Rarely, radiotherapy (RT) has been reported as a localised trigger factor for BP. Case: We present a case of a 64-year-old woman who underwent radical mastectomy and radiation therapy for breast cancer. Two months after the completion of RT with adjuvant Trastuzumab, a BP eruption developed in the irradiated area, spreading thereafter to other skin areas. The patient wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A total of 13 residual articles fulfilling the inclusion criteria were included in the present review update. Table 1 summarizes the main characteristics of the selected studies (4)(5)(6)(7)(11)(12)(13)(14)(15)(16)(17)(18)(19). Eleven articles are case reports (4)(5)(6)(7)11,(13)(14)(15)(16)18,19), while a case series of 2 patients was provided by Shon et al (12).…”
Section: Update Of Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 13 residual articles fulfilling the inclusion criteria were included in the present review update. Table 1 summarizes the main characteristics of the selected studies (4)(5)(6)(7)(11)(12)(13)(14)(15)(16)(17)(18)(19). Eleven articles are case reports (4)(5)(6)(7)11,(13)(14)(15)(16)18,19), while a case series of 2 patients was provided by Shon et al (12).…”
Section: Update Of Literature Reviewmentioning
confidence: 99%
“…Table 1 summarizes the main characteristics of the selected studies (4)(5)(6)(7)(11)(12)(13)(14)(15)(16)(17)(18)(19). Eleven articles are case reports (4)(5)(6)(7)11,(13)(14)(15)(16)18,19), while a case series of 2 patients was provided by Shon et al (12). Hung et al (17), reported the first large-scale case-control study in 2019, focusing on the relationship between the development of autoimmune blistering disease among patients mainly affected by breast cancer and treated with RT.…”
Section: Update Of Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation